2021
DOI: 10.3390/cells10113159
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cellular Factors Required for SARS-CoV-2 Replication

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the recently emerged virus responsible for the COVID-19 pandemic. Clinical presentation can range from asymptomatic disease and mild respiratory tract infection to severe disease with lung injury, multiorgan failure, and death. SARS-CoV-2 is the third animal coronavirus to emerge in humans in the 21st century, and coronaviruses appear to possess a unique ability to cross borders between species and infect a wide range of organisms. This is somewha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…This is also the reason why, in the current work, further studies were focused on the activity of P. galeata CCNP1313 metabolites against SARS-CoV-2. For this purpose, the human lung epithelial cell line A549 ACE2/TMPRSS2 overexpressing the angiotensin-converting enzyme 2 (ACE2), and the transmembrane serine proteases TMPRSS2, crucial for the SARS-CoV-2 spike protein priming was used [ 42 , 43 ]. A549 ACE2/TMPRSS2 cells recapitulate the natural route of entry for the coronavirus, which enters through fusion directly on the cell surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is also the reason why, in the current work, further studies were focused on the activity of P. galeata CCNP1313 metabolites against SARS-CoV-2. For this purpose, the human lung epithelial cell line A549 ACE2/TMPRSS2 overexpressing the angiotensin-converting enzyme 2 (ACE2), and the transmembrane serine proteases TMPRSS2, crucial for the SARS-CoV-2 spike protein priming was used [ 42 , 43 ]. A549 ACE2/TMPRSS2 cells recapitulate the natural route of entry for the coronavirus, which enters through fusion directly on the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…A549 ACE2/TMPRSS2 cells recapitulate the natural route of entry for the coronavirus, which enters through fusion directly on the cell surface. As a result, this makes the virus independent of the endocytic machinery and cellular cathepsins [ 43 ]. Similarly to cytotoxic effects, the antiviral activity was recorded in fractions eluted with solvent of different MeOH content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify the mechanisms through which the symptoms caused by COVID-19 manifest, studies were conducted using cell-based in vitro or animal-based in vivo models [22,23]. It has been found that angiotensin-converting enzyme 2 (ACE2), a cell membrane protein, contributes to the introduction of SARS-CoV-2 into the cell [23].…”
Section: Introductionmentioning
confidence: 99%
“…Our screens revealed several pro-viral genes shared by SARS-CoV, SARS-CoV-2, and MERS-CoV in both Vero-E6 and Calu-3 cells 22,23 . Other genome-wide CRISPR/Cas9 screens for SARS-CoV-2 and other related coronaviruses have since identified additional host dependency factors including proteins involved in viral entry, endocytic trafficking and sorting, cholesterol homeostasis, and autophagy [27][28][29][30][31][32] . While reproducibility between screens was excellent when performed on the same cell type, there was otherwise limited overlap across hits in these loss of function screens [27][28][29][30][31][32] .…”
Section: Introductionmentioning
confidence: 99%